Caminhos da liberdade: história e memória dos quilombolas da Tabacaria (Palmeira dos índios/AL). - Maria Neta, Francisca (2020)
Since the second half of the twentieth century with the advent of re-democratization and promulgation of the 1988 Constitution in Brazil, the remaining quilombola communities have started the claims for ethnic recognition and land possession. One of the regions within the country that this claiming situation has been present is the municipality of Palmeira dos Índios in the northeastern state of Alagoas, where the Remaining Community of Quilombos is located, so called Tabacaria, that is the object of this study, which purpose is to research how this community develops the process of territorialization re-signified through its identity and memory practices. In order to develop such research, we follow the concepts of collective and individual memory presented by Joel Candau (2012) and Maurice Halbwachs (2006), material and immaterial heritage, according to the theoretical assumptions of Françoise Choay (2006) and François Hartog (2015) based on the discussion concerning territory carried out by Raffestin (1993), who have been working in accordance to the discussion on Afro-Brazilian peoples presented by Dirceu Lindoso (2007), Alberti (2005) and Hebe Matos (2005). The methodology was based on analysis of documentary sources: letters, photographs, maps, newspapers, documents produced by the institutional bodies for the recognition of the community (INCRA and Fundação Cultural Palmares), and oral history resources: interviews, surveys, and reports of life experience by elderly members, community leaders and representatives from government agencies. The purpose of this work is to present identity practices related to collective and individual memories in the re-signification of a territory linked to the historical and ethnic legitimacy of the quilombolas from Tabacaria. In addition to the development of the dissertation, a documentary was produced (21 minutes long) entitled: “Tobacco shop: identities, memories and territories” in which the results from the research are synthesized and presented as a pedagogical and dissemination resource for the academic community and the society in general